Enzymatic additives and their use on animal rearing - Valdivia, Aymara L.; Matos, Madyu; Martínez, Soraya; Pérez, Y.; Rubio, Yasmary; Vega, J. (Cuban Journal of Agricultural Science, 2019)
Animal production in recent years has been marked by the increase in the prices of raw materials used in food. To face this situation, the challenge is to achieve better use of the diets provided to animals. For this purpose, one of the most used strategies in the world is the use of enzymatic additives, which are obtained by submerged fermentation or by solid phase fermentation, from bacteria or fungi. Among the hydrolytic enzymes that are used in the supplementation of monogastric species, those that participate in the degradation of antinutritional factors, such as non-starch polysaccharides (NSP), stand out. Its use increases food digestibility, improves its quality and use, and favors the degradation of compounds that interfere with nutrient digestion and utilization. The application of these products has a positive impact on productive indicators and health in poultry and pigs, but the effectiveness of their use depends, among other factors, on the composition and quality of diet. This paper aims to provide updated scientific information on obtaining hydrolytic enzymes and their use in the feeding of monogastric species. Keywords: animal feed, hydrolytic enzymes, non-starchy polysaccharides